2001
DOI: 10.1021/nl0155882
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclusters of Iridium Oxide and of Rhodium Oxide Supported on MgO

Abstract: MgO-supported Ir 4 and Rh 6 , prepared from [Ir 4 (CO) 12 ] and [Rh 6 (CO) 16 ], respectively, on MgO, were partially oxidized at 323 K, with partial destruction of the metal frames, and reformed by treatment in H 2 . Oxidation at higher temperatures resulted in total oxidation of the clusters with breakup of the metal frames, and treatment in H 2 led to near reconstruction of the metal clusters, but with some migration and aggregation. The results imply that the oxidized nanoclusters were site isolated on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
(44 reference statements)
2
20
0
Order By: Relevance
“…After deposition of the metal compound, the catalyst is commonly activated through removal of the ligands in treatments with hydrogen (reduction) or oxygen (calcination). The effect of the activation procedure on iridium catalyst has earlier been studied by Lai et al [4] and Cunha et al [5]. Lai et al [4] showed that, at 250°C, oxygen causes oxidation and fragmentation of Ir 4 clusters prepared from Ir 4 (CO) 12 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…After deposition of the metal compound, the catalyst is commonly activated through removal of the ligands in treatments with hydrogen (reduction) or oxygen (calcination). The effect of the activation procedure on iridium catalyst has earlier been studied by Lai et al [4] and Cunha et al [5]. Lai et al [4] showed that, at 250°C, oxygen causes oxidation and fragmentation of Ir 4 clusters prepared from Ir 4 (CO) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the activation procedure on iridium catalyst has earlier been studied by Lai et al [4] and Cunha et al [5]. Lai et al [4] showed that, at 250°C, oxygen causes oxidation and fragmentation of Ir 4 clusters prepared from Ir 4 (CO) 12 . After exposure of the oxidized and fragmented Ir 4 clusters to hydrogen at 300°C, the original Ir 4 clusters are reconstructed with a minor degree of aggregation [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…76 The most energetically favorable was the near tetrahedral configuration with three iridium atoms bound to the surface. 77,78 ESI Fig. S21a† was chosen to be our representative Ir 4 cluster.…”
Section: Methodsmentioning
confidence: 99%